A 277 year cool season dam inflow reconstruction for Tasmania, southeastern Australia. Issue 1 (17th January 2017) - Allen, K. J.; Nichols, S. C.; Evans, R.; Allie, S.; Carson, G.; Ling, F.; Cook, E.R.; Lee, G.; Baker, P. J.
Abstract: Seasonal variability is a significant source of uncertainty in projected changes to precipitation across southeastern Australia (SEA). While existing instrumental records provide seasonal data for recent decades, most proxy records (e.g., tree rings, corals, speleothems) offer only annual reconstructions of hydroclimate. We present the first cool‐season (July–August) reconstruction of dam inflow (Lake Burbury) for western Tasmania in SEA based on tree‐ring width ( Athrotaxis selaginoides ) and mean latewood cell wall thickness ( Phyllocladus aspleniifolius ) chronologies. The reconstruction, produced using principal component regression, verifies back to 1731 and is moderately skillful, explaining around 23% of the variance. According to the reconstruction, relatively low inflow periods occurred around 1860, the early 1900s and 1970, while relatively high inflows occurred in the 1770s and 1810s. Highest reconstructed inflows occurred in 1816, and lowest in 1909. Comparison with available documentary and instrumental records indicates that the reconstruction better captures high rather than low flow events. There is virtually no correlation between our reconstruction and another for December–January inflow for the same catchment, a result consistent with the relationship between seasonal instrumental data. This suggests that conditions in one season have not generally reflected conditions in the other season over the instrumental record, or for the past 277 years. This illustrates the value of obtaining reconstructions of regional hydroclimatic variability for multiple individual seasons in regions where dry and wet seasons are not strongly defined. The results also indicate that the hydroclimate of the southeastern Australian region cannot be adequately represented by a single regional reconstruction. Key Points: First cool season hydroclimatic reconstruction for southeastern Australia shows drier conditions more common in most recent 150 years Recent July–August hydroclimate within natural variability of the past 277 years Latewood cell wall thickness chronology most important predictor in model